SOLUTION
Let the consecutive integers be x, y, and z
Since the first integer "x" is subtracted from 111, that becomes
111 - x
Now, the result of subtraction is equal to the sum of the second and third. This becomes
111 - x = y + z
Since they are consecutive, it means that
y = x + 1 and z = x + 2
So
![\begin{gathered} 111-x=y+z \\ 111-x=(x+1)+(x+2) \\ 111-x=x+1+x+2 \\ \text{Collecting like terms we have } \\ 111-1-2=x+x+x \\ 108=3x \\ (108)/(3)=(3x)/(3) \\ \\ x=36 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/si2zjdgrvnl9txxvlvh25bqf0iu9kpzu0a.png)
![\begin{gathered} y=x+1 \\ y=36+1 \\ \\ y=37 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wwsxh51xh4q3ilv8rtbad608ze97fms2c1.png)
![\begin{gathered} z=x+2 \\ z=36+2 \\ \\ z=38 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/36sphkst4d0vuv6wasd1gmu9jqdx34c6pk.png)
Therefore, the integers are 36, 37 and 38